2007
DOI: 10.1163/156856207780425040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface modification of polymer beads on the mechanical properties of acrylic bone cement

Abstract: The effect of surface modification of polymer filler on the static mechanical properties of acrylic bone cement was studied. The surface of polymer beads was modified with carboxylic and amino groups by photochemical reaction with azide compounds. Monomer modifiers (maleic anhydride, methacrylic acid and p-aminostyrene) are attached to the functionalized surface of polymer beads. Functional allyl groups, which are capable of the graft polymerisation reaction, are attached to the surface via photochemical react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…As other investigators reported, the transition of force between matrix and PMMA granules depends on adhesion quality of interface. In fact, imperfect adhesion causes pseudo voids [19]. Figure 7 is concerned with the fracture surfaces of the composite sample.…”
Section: Resultsmentioning
confidence: 99%
“…As other investigators reported, the transition of force between matrix and PMMA granules depends on adhesion quality of interface. In fact, imperfect adhesion causes pseudo voids [19]. Figure 7 is concerned with the fracture surfaces of the composite sample.…”
Section: Resultsmentioning
confidence: 99%
“…mechanical [1], thermal [2] or biological [3][4][5][6]) for specific applications have been recognized as a very promising field in material sciences. More specifically, the polymeric materials are very attractive due to their multifarious possible variations in the nature (or ratio) of the initial monomer(s), synthesis method, catalysts, final processing etc.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the polymeric materials are very attractive due to their multifarious possible variations in the nature (or ratio) of the initial monomer(s), synthesis method, catalysts, final processing etc. to provide new materials with specific properties [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%